Managing Local Employees in International Joint Ventures in China: A Case Study - Liu, Liheng (2007)
International Joint Ventures (IJVs) are considered as one of the favourable enter modes for foreign firms to operate their business in China, with the special consideration of government preference and potential benefits from local partners. However, due to different human resource management practices, national cultures and social institutional arrangements between foreign firms and their Chinese partners, some problems have emerged when IJVs manage their local employees in China.